Up‐regulation of NKX3.1 Expression and Inhibition of LNCaP Cell Proliferation Induced by an Inhibitory Element Decoy - JIANG, An‐Li; HU, Xiao‐Yan; ZHANG, Peng‐Ju; HE, Mei‐Lan; KONG, Feng; LIU, Zhi‐Fang; YUAN, Hui‐Qing; ZHANG, Jian‐Ye (Acta biochimica et biophysica Sinica, 2005)
NKX3.1 is an androgen‐regulated prostate‐specific homeobox gene that is thought to play an important role in prostate development and cancerogenesis. NKX3.1 acts as a tumor suppressor gene specifically in the prostate. Up‐regulation of NKX3.1 gene offers a promising gene therapy for prostate cancer. The decoy strategy has been developed and is considered a useful tool for regulating gene expression and gene therapy. In our previous studies, we identified a 20 bp inhibitory element upstream of the NKX3.1 promoter. In this study, we focused on using the 20 bp inhibitory element decoy to block negative regulation of the NKX3.1 gene and to up‐regulate NKX3.1 expression using synthetic double‐stranded oligodeoxynucleotides of the 20 bp inhibitory element. We found in an electrophoretic mobility shift assay experiment that the 20 bp inhibitory decoy presented competitive binding to a specific binding protein of the 20 bp inhibitory element in prostate cancer cell line LNCaP. In luciferase reporter gene assays, we found that the 20 bp inhibitory decoy could enhance NKX3.1 promoter activity, and RT‐PCR and Western blot analysis revealed that NKX3.1 expression was up‐regulated effectively by the transfection with the 20 bp inhibitory decoy. Furthermore, cell proliferation was inhibited by up‐regulated NKX3.1 expression induced by the 20 bp inhibitory decoy. Edited by Ding‐Gan LIU